2005
DOI: 10.1016/j.febslet.2005.02.078
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cys‐295 on subunit interactions and allosteric regulation of phosphofructokinase‐2 from Escherichia coli

Abstract: In a previous work, chemical modification of Cys-238 of Escherichia coli Pfk-2 raised concerns on the importance of the dimeric state of Pfk-2 for enzyme activity, whereas modification of Cys-295 impaired the enzymatic activity and the MgATP-induced tetramerization of the enzyme. The results presented here demonstrate that the dimeric state of Pfk-2 is critical for the stability and the activity of the enzyme. The replacement of Cys-238 by either Ala or Phe shows no effect on the kinetic parameters, allosteric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…27 A homodimer is observed in the asymmetric unit, which makes extensive contacts with a symmetry-related mate (Fig. 2), forming what appears to be the tetramer under the abovementioned conditions.…”
Section: Intersubunit Interactionsmentioning
confidence: 91%
“…27 A homodimer is observed in the asymmetric unit, which makes extensive contacts with a symmetry-related mate (Fig. 2), forming what appears to be the tetramer under the abovementioned conditions.…”
Section: Intersubunit Interactionsmentioning
confidence: 91%
“…Site‐directed mutagenesis is a standard experimental technique used to generate site‐specific mutations in known protein‐coding genes . By deleting or substituting particular residues, the role of individual amino acids in the reaction mechanisms of enzymes or in the structural configuration of proteins can be studied . However, this technique is very laborious and time consuming, and in silico tools to help direct the selection of candidate residues are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…[18] By deleting or substituting particular residues, the role of individual amino acids in the reaction mechanisms of enzymes or in the structural configuration of proteins can be studied. [19][20][21][22][23] However, this technique is very laborious and time consuming, and in silico tools to help direct the selection of candidate residues are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Light scattering and gel filtration analyses [12,13] have shown that E. coli Pfk‐2 is primarily a dimer in solution, which quaternary structure is required for enzymatic activity [12,14]. As shown by its crystal structure (PDB ID code 3CQD), each subunit can be divided in two parts: the conserved α/β/α domain and the additional β‐sheet structural element that protrudes from it.…”
Section: Introductionmentioning
confidence: 99%